FAKTOR-FAKTOR YANG MEMENGARUHI IMPLEMENTASI KEBIJAKAN PENANGGULANGAN PERTAMBANGAN EMAS TANPA IJIN DI KECAMATAN SEPANG KABUPATEN GUNUNG MAS KALIMANTAN TENGAH - Anyualatha Haridison (Jurnal Universitas Paramadina, 2013)
AbstractThe study investigates factors that affect the implementation of policy inhibiting the gold mining without a permit (PETI or Pertambangan Emas Tanpa Ijin). Using qualitative methods, the study analyzes different perspective of several key informants. Based on the results, it can be noted several factors that affect: (a) socio-economic conditions are still poor. Tapping rubber is still not fully able to meet the educational needs of their children, so that the gold mining is still an option for the community; (b) determination of the people of the mining area has still not finished cause spatial planning Central of Kalimantan hasn’t clear; (c) coordination between institutions is still weak, both intergovernmental districts of Sepang, with mining department and government of Gunung Mas region, proved yet issued regulations on prevention PETI; (d) resources are limited, relate to the supervision of the gold mining activities in the district of Sepang. The government can do it, to publishing a special regulation about prevention of PETI immediately that contents it leads to protection of law and public access to managemet of gold natural resources.Keywords : implementasi, kebijakan, PETI